2021
DOI: 10.1039/d1ra04946a
|View full text |Cite
|
Sign up to set email alerts
|

Ternary 3D reduced graphene oxide/Ni0.5Zn0.5Fe2O4/polyindole nanocomposite for supercapacitor electrode application

Abstract: A facile two-step strategy has been reported for the preparation of a ternary 3D reduced graphene oxide/Ni0.5Zn0.5Fe2O4/polyindole nanocomposite (GNP) and this composite is applied as an electrode material for supercapacitor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…The D band (1352 cm –1 ) associated with vibrations of the sp3 carbon atoms in disordered graphite and the G band (1597 cm –1 ) related to the in-plane vibration of the sp 2 carbon atoms in a 2D hexagonal lattice are observed for the G aerogel . Furthermore, a 2D band was also observed at 2672 cm –1 along with a defect activated peak called D + G (2885 cm –1 ) in the spectrum . The Raman spectrum of the PIN aerogel displayed two typical D and G bands at ∼1330 and ∼1590 cm –1 , respectively, which are assigned to the C–N stretching mode and aromatic characteristic symmetric and asymmetric backbone stretching mode of the C–C bond, respectively. , In the case of the PG aerogel, the appearance of the characteristic D and G bands of the PIN and G aerogels at 1352 and 1590 cm –1 indicates the successful synthesis of the PG aerogel.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The D band (1352 cm –1 ) associated with vibrations of the sp3 carbon atoms in disordered graphite and the G band (1597 cm –1 ) related to the in-plane vibration of the sp 2 carbon atoms in a 2D hexagonal lattice are observed for the G aerogel . Furthermore, a 2D band was also observed at 2672 cm –1 along with a defect activated peak called D + G (2885 cm –1 ) in the spectrum . The Raman spectrum of the PIN aerogel displayed two typical D and G bands at ∼1330 and ∼1590 cm –1 , respectively, which are assigned to the C–N stretching mode and aromatic characteristic symmetric and asymmetric backbone stretching mode of the C–C bond, respectively. , In the case of the PG aerogel, the appearance of the characteristic D and G bands of the PIN and G aerogels at 1352 and 1590 cm –1 indicates the successful synthesis of the PG aerogel.…”
Section: Resultsmentioning
confidence: 95%
“…The D/G intensity ratios of all samples were estimated and were in the order of PIN aerogel (0.712) < G aerogel (0.785) < carbon black (0.942). The PG aerogel sample had the highest D/G intensity ratio compared to PIN aerogel and G aerogel samples, which further confirms the interfacial interaction between the graphitic plane and PIN chains in the hybrid, which affected the Raman peaks …”
Section: Resultsmentioning
confidence: 99%
“…In the first stage (30–95 °C), the weight loss of the samples is caused by the evaporation of moisture and dopant in the polymer, 60 whereas the second stage (350–850 °C), major weight loss, results from the thermal degradation of the PIN polymer chain. 61 At 850 °C, PIN retains only 6.4% of the initial weight, which reveals high thermal degradability of the PIN backbones. The weight residual of the nanocomposites with Ni 1– x Zn x Fe 2 O 4 ( x = 0, 0.5, 1) with loadings of 5, 10, and 15 wt % are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that there are two-stage degradations in the pure PIN and its nanocomposites. In the first stage (30–95 °C), the weight loss of the samples is caused by the evaporation of moisture and dopant in the polymer, whereas the second stage (350–850 °C), major weight loss, results from the thermal degradation of the PIN polymer chain . At 850 °C, PIN retains only 6.4% of the initial weight, which reveals high thermal degradability of the PIN backbones.…”
Section: Resultsmentioning
confidence: 99%
“…Highly intense oxidation peak was also observed in the electrochemical investigation at 1.02 V indicating reversible redox charge storage electrochemical kinetics. As the scan rate decreases to 10 mV/s, the height of cathodic and anodic peak currents decreases, which indicating a shift of pseudocapacitive to capacitive behavior [46]. Fig.…”
Section: Liquid Configured Symmetric Devicementioning
confidence: 87%